Dementia and place practices, experiences and connections - Ward, Richard 1966-; Clark, Andrew 1978-; Phillipson, Lyn ca. 20./21. Jh (Policy Press, 2021)
Giving voice to the lived experiences of people with dementia across the globe, this text highlights the challenges presented as dementia care shifts to a community setting. Contributors address the social aspects of environment and, using a unique 'neighbourhood-centred' perspective, provide an innovative guide for policy and practice